Turiel, Antonio (2022). Sense energia. Breu guia per al Gran Descens - Ferrer Gallardo, Xavier (Documents d’Anàlisi Geogràfica, 2023)
Turiel, Antonio (2022). Sense energia. Breu guia per al Gran Descens Madrid: Alfabeto, 105 p. ISBN 978-84-17951-34-4